Achieving WHO's Goal for Reducing Cesarean Section Rate in a Chinese Hospital - Ji, Yan-Jie; Wang, Hai-Bo; Bai, Zhi; Long, Da-Jian; Ma, Kaidong; Yan, Jie; Li, Yun-Xiu; Wu, Yang-Feng; Yang, Huixia (Frontiers in Medicine, 2021)
Background: To address the worldwide dramatically increased caesarean section (CS) rate in the past decades, the World Health Organization (WHO) has recommended the CS rate should not be higher than 10-15%. Whether it is achievable remains unknown. Methods: We collected data of delivery from 2008 to 2017 in two typical regional hospitals in China: Longhua Hospital (national policies rigorously implemented) and Dongguan Hospital (national policies not rigorously implemented). We compared between two hospitals the 10 years trend in annual rate of CS, standardized by age, education level, parity and CS history, against the time of issuing relevant national, local, and hospital policies. Results: 42441 women in Longhua and 36935 women in Dongguan gave birth in the 10 years. China’s first national policy on CS reduction was issued in 2010 and the formal relaxation of one-child policy was in 2015-16. The standardized annual CS rate was around 35% in 2008-09, declined sharply since 2010 down to 13.1% in 2016 (p for trend <0.001) and leveled off then in Longhua. In contrast, the rate stayed around 25% at the beginning, increased to 36% in 2011, decreased sharply to 27% in 2012 and leveled off until 2015 (p for trend <0.001), and then bounced back to 35% in 2017 in Dongguan. Proportion of women with history of CS increased significantly in two hospitals (both roughly from 6% before 2010 to 20% after 2015). Analyses stratified by modified Robson classification showed that CS rates reduced in all risk classes of delivery women in Longhua but only in the Robson class 2 group in Dongguan. Major complications did not differ by hospital. Conclusions: With vigorously implementing national policies at micro levels, the WHO recommended CS rate could be achieved without increase in major complications. Funding: The study was funded by Guangdong Provincial Science and Technology Plan (2017A020214007) and Dongguan Technology Development Society (201950715032188).